The Transition to Middle School is Associated with Changes in the Developmental Trajectory of ADHD Symptomatology in Young Adolescents with ADHD - Joshua M. Langberg; Jeffery N. Epstein; Mekibib Altaye; Brooke S. G. Molina; L. Eugene Arnold; Benedetto Vitiello (2008)
The attention deficit hyperactivity disorder (ADHD) symptom presentation of young adolescents with ADHD was examined in association with the transition to middle school. This study used data collected in the Multimodal Treatment Study of ADHD, which included children between 7 and 9 years of age with a diagnosis of ADHD (n = 258) and grade- and sex-matched controls (n = 112). The trajectory of ADHD symptoms before, during, and after the transition to middle school was modeled using hierarchical linear modeling. A clear developmental reduction in ADHD symptomatology was observed for all three ADHD symptom domains. For young adolescents with ADHD, the transition to middle school was associated with a disruption in the developmental decline of inattention, hyperactivity, and impulsivity symptoms as measured by parent ratings. This effect was also observed for teacher ratings of inattention and hyperactivity. These results support the assertion that the environmental changes associated with transitioning to middle school coincide with a transient reversal in ADHD symptom decline among children with ADHD.